2008
DOI: 10.1200/jco.2007.11.6699
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Weekly Compared With Every-3-Weeks Paclitaxel for Metastatic Breast Cancer, With Trastuzumab for all HER-2 Overexpressors and Random Assignment to Trastuzumab or Not in HER-2 Nonoverexpressors: Final Results of Cancer and Leukemia Group B Protocol 9840

Abstract: Weekly paclitaxel is more effective than every-3-weeks administration for MBC. Trastuzumab did not improve efficacy for HER-2 nonoverexpressors. Neurotoxicity is a treatment-limiting toxicity for weekly paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
344
4
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(369 citation statements)
references
References 27 publications
10
344
4
11
Order By: Relevance
“…As paclitaxel neurotoxicity is dose-dependent, 13 we calculated the accumulated paclitaxel dose that produced clinically relevant neurotoxicity, rather than just evaluating the presence or lack of neurotoxicity at the end of the treatment. We confirmed that the more dose intense paclitaxel schedule of 80-90 mg m À2 weekly was a risk factor for the neurotoxicity 8,9 and, although previous results concerning age are inconclusive, 12,13,40 we found that patients below 50 years developed greater neuropathy (Supplementary Figure 1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As paclitaxel neurotoxicity is dose-dependent, 13 we calculated the accumulated paclitaxel dose that produced clinically relevant neurotoxicity, rather than just evaluating the presence or lack of neurotoxicity at the end of the treatment. We confirmed that the more dose intense paclitaxel schedule of 80-90 mg m À2 weekly was a risk factor for the neurotoxicity 8,9 and, although previous results concerning age are inconclusive, 12,13,40 we found that patients below 50 years developed greater neuropathy (Supplementary Figure 1).…”
Section: Discussionsupporting
confidence: 81%
“…6,7 Neurotoxicity, which has become the dose-limiting toxicity of paclitaxel, exhibits substantial interindividual variability. This toxicity is dose-dependent and more frequent in weekly paclitaxel regimens, 8,9 in patients with diabetes, previous neurotoxic chemotherapy treatments and in patients with pre-existing neuropathies. 10,11 Age and gender might also be risk factors [11][12][13] and decreased levels of plasma nerve factors might have a role in the neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Its superiority over the standard 3-weekly administration (175 mg/m 2 over 3-h infusion) was demonstrated in a randomized study [23], conducted by the Cancer and Leukemia Group B (CALGB). In that study, weekly paclitaxel was found to be superior to the 3-weekly regimen in terms of ORR (42% vs 29%, P = 0.0004) and TTP (9 months vs 5 months, P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most studies of neoadjuvant Nab-PTX in breast cancer reported on the every-3-week (q3w) Nab-PTX administration regimen (16,17,(19)(20)(21) (22). Chemotherapy agents, including taxanes, which are recommended in the metastatic (23) and adjuvant settings (24), are also considered in the neoadjuvant setting.…”
Section: Discussionmentioning
confidence: 99%